Current concepts in the management of enterocutaneous fistula - Dodiyi-Manuel, Amabra; Wichendu, Promise N. (International Surgery Journal, 2018)
Enterocutaneous fistula is an abnormal connection between the intra-abdominal gastrointestinal tract and skin. It causes considerable morbidity and mortality. The goals of management are restoration of gastrointestinal continuity and allowance of enteral nutrition with minimal morbidity and mortality. A multidisciplinary approach is essential in the successful management and this has led to closure rates ranging from 5-20% following conservative management and 75-85% with operative treatment. This article seeks to review the current concepts in the management of enterocutaneous fistula. A systematic search of literature on enterocutaneous fistula was conducted. Relevant materials were selected and selected references from relevant books, journal articles and abstracts using Medline, Google scholar and Pubmed databases were critically reviewed. Enterocutaneous fistulas can be classified by the anatomy, aetiology or physiology. Anatomically, enterocutaneous fistula has been classified based on the organ of origin and this is useful in the consideration of management options: type l (abdominal oesophageal and gastroduodenal fistula), type ll (small bowel fistula), type lll (large bowel fistula) and type IV (enteroatmospheric, regardless of origin. The anatomy also depends on the presence or absence of associated abscess cavity and the length and characteristics of the fistula tract. Aetiologically, the majority of enterocutaneous fistulas are iatrogenic (75-85%) while between 15 and 25% occur spontaneously. The physiological classification is based on the volume of its output. High output fistulas drain more than 500mls in 24 hours, moderate output between 200 and 500mls in 24 hours and low output less than 200mls in 24 hours. Successful management requires a multidisciplinary approach and would consist of initial resuscitaion with fluids and electrolytes, control of sepsis, good and adequate nutrition, wound care and skin protection and definitive management. The treatment of enterocutaneous fistula is multidisciplinary and remains a challenge despite the recent improvement in supportive care. Once enterocutaneous fistula occurs, adequate stabilization of the patient and non-operative management should be commenced. If surgery is required, careful planning, meticulous dissection, restoration of bowel continuity and reconstruction of abdominal wall are critical.